Two-way Affect Loops in multimedia experiences - Pike, Matthew; Ramchurn, Richard; Wilson, Max L. (ACM, 2015)
A users interaction with a film typically involves a One Way Affect (1WA), in which the film being consumed has an affect on the consumer. Recent advances in physiological monitoring technology however has facilitated the notion of a Two Way Affect Loop (2WAL), in which a film piece can be dynamically affected by a consumers physiology or behaviour. This paper outlines an agenda for further investigating 2WAL, setting research questions and the influence of related research areas.